Taḥlīl al-Irtibāţ baina Idārah al-Mawārid al-Basyariyyah wa al-Mu’ammāriyyah al-Riyādiyyah: Dirāsah Maidāniyyah fī al-Manẓūmār al-Ĥukūmiyyah bi Idārah Zakho al-Mustaqillah - Mustafa, Buhar Hassan; Sultan, Hikmat Rashid; Ismail, Jagar Mustafa (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
This study aims to analyze and understand the nature of the relationship between digital human resource management and entrepreneurial architecture in government organizations within Zakho Independent Administration, in light of the increasing challenges posed by the modern digital environment. The study was based on a main hypothesis stating the existence of a positive significant correlation between digital human resource management and entrepreneurial architecture, along with sub-hypotheses that addressed the links between the sub-dimensions of both variables. The researcher employed a descriptive-analytical approach, relying on multiple correlation analysis using Spearman's correlation coefficient, and applied a questionnaire to a random sample of managers and employees in government administrations. The results of statistical analysis revealed a strong positive and statistically significant correlation between digital human resource management and entrepreneurial architecture (overall correlation coefficient = 0.606, at significance level 0.01). The results also showed variation in the strength of relationships between the sub-dimensions of the two variables, with observed weakness or non-significance in the relationship between some dimensions, particularly between digital evaluation and entrepreneurial design dimensions. The study concluded with a set of findings and recommendations focusing on the necessity of developing integrated policies to enhance the integration between digital human resource management and entrepreneurial architecture, and the importance of investing in human capital and modern technology to achieve institutional excellence in the government sector.